Antioxidant Potency of Cassumunin A-C Compounds from Bangle Rhizome (Zingiber cassumunar) by Molecular Docking on Human ROS-1 kinase Receptors - Dwi Utami; Wahyu Yuliana Solikah; Nurkhasanah Mahfudh (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2021)
Antioxidants play an  role in human health by fighting oxidative stress and preventing chronic disease. Nowadays, molecular docking is used  Bangle rhizome (Zingiber cassumunar) has  a derivative of curcuminoid, cassumunin A, cassumunin B, and cassumunin C. This study was designed to determine the value of binding affinities between cassumunins ligands on human ROS1 kinase receptors, related to their antioxidant activity with ascorbic acid and tocopherol. One set of computational programs is Autodock Tools, Biovia Discovery Studio, and Command Prompt has prepared. These docking results presented the binding affinity values of cassumunin A, cassumunin B, cassumunin C, ascorbic acid, and tocopherol were -9.4 kcal/mol, -9.7 kcal/mol, -9.0 kcal/mol, -5.2 kcal/mol, and -8.1 kcal/mol respectively. RMSD value for the five ligands was ≤ 2Å, showed the validity of the docking results. Cassumunin A-C compound  higher affinity compared to ascorbic acid and tocopherol. Based on this computational study, cassumunin A-C the potential compounds to be developed as potent antioxidant agents from natural resources.